Pengaruh Digitalisasi Akuntansi Sektor Publik Dan Kompetensi Aparatur Keuangan Terhadap Akuntabilitas Dana Bantuan Sosial Dengan Peran Budaya Birokrasi Sebagai Variabel Moderasi - Mutmainah Mutmainah; Rudy Usman; Muhammad Din; Lucyani Meldawati (SAFE-Network, 2026)
This study aims to analyze the influence of public sector accounting digitalization and financial apparatus competency on the accountability of social assistance funds, with bureaucratic culture as a moderating variable. The approach used is quantitative with associative research type. The data used consists of primary and secondary data. Primary data was obtained by distributing questionnaires to 34 respondents who are apparatus at the Social Service of Parigi Moutong Regency involved in the management of social assistance funds, while secondary data was obtained from related documents at the agency. The data analysis technique used Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of WarpPLS software. The results of the study indicate that public sector accounting digitalization does not significantly affect the accountability of social assistance funds. The competence of financial apparatus has a positive and significant effect on accountability. Bureaucratic culture does not act as a moderating variable in the relationship between accounting digitalization and financial apparatus competency on accountability. This study shows that increasing accountability in the management of social assistance funds is more influenced by the quality of human resources than by the implementation of digital systems. This finding emphasizes the importance of strengthening apparatus competency in supporting accountable public financial management.